2005
DOI: 10.1111/j.1365-2044.2005.04222.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of accidental dural puncture during labour epidural analgesia: a survey of UK practice*

Abstract: Summary The management of accidental dural puncture and postdural puncture headache in obstetric practice continues to be of great interest. This survey aims to explore the current management of this complication in the United Kingdom and compares the findings to a similar survey undertaken in 1993. A postal questionnaire was sent to all maternity units (n = 248). The return rate was 71%. Of these, 144 units (85%) now have written guidelines for the management of accidental dural puncture compared to 58% in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 28 publications
5
55
0
5
Order By: Relevance
“…The first reference cited by Patel and Chatterjee [1] was cited in our reply because it was used by Cook et al to 'support the overall safety of the laryngeal mask airway' [2]. We are in full agreement with Patel and Chatterjee that the laryngeal mask airway has had a remarkable record of safe use since its introduction.…”
Section: A Replysupporting
confidence: 64%
See 2 more Smart Citations
“…The first reference cited by Patel and Chatterjee [1] was cited in our reply because it was used by Cook et al to 'support the overall safety of the laryngeal mask airway' [2]. We are in full agreement with Patel and Chatterjee that the laryngeal mask airway has had a remarkable record of safe use since its introduction.…”
Section: A Replysupporting
confidence: 64%
“…We read with interest Drs Christie and Ball's report concerning a problem with adhesive surgical drapes during ENT surgery [1], resulting in inadvertent premature extubation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although autologous epidural blood patch is the definitive treatment for PDPH and the failure of this procedure is relatively rare, it may not be effective in a significant proportion of patients [6,[10][11][12]. Baraz et al undertook a postal questionnaire of UK obstetric units, and found that only 26% treated PDPH with an epidural blood patch as soon as it was diagnosed, whereas in 71% of units, the blood patch was only performed once conservative measures had failed [13]. There are two widely held theories, which are somewhat competing, to account for the onset of the headache.…”
Section: Discussionmentioning
confidence: 99%
“…However, placement of an autologous epidural blood patch may result in both a potential blood infection of the central nervous system [4,5] and a second unintentional dural puncture during attempts to reposition the epidural needle. That concern has compelled anesthesiologists to search for therapeutic modalities that involve less risk [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%